Relevance between Blended Learning and Students' Independent Learning Curriculum : An Overview of Digital Age Education, Student and Teacher Engagement, Technological Resources. - Pramesworo, Ignatius Septo; Fathurrochman, Irwan; Sembing, Darmawanta; Bangkara, B.M.A.S Anaconda; Sudrajat, Didi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to explore the relevance between blended learning and students' independent learning curriculum in the digital age. This study used a descriptive method with a qualitative approach to gather and analyze data from diverse participants. Multiple data collection techniques were utilized to ensure a comprehensive and in-depth exploration of the research topic. The sample included teachers from different educational levels, students with varying academic backgrounds, and educational administrators with experience in curriculum development and implementation. Procedures Data analysis involved several iterative steps. Based on the research results, it was found that a strong connection between blended learning and promoting independent learning skills among students. Challenges were identified in effectively incorporating an independent learning curriculum within the blended learning environment. The study highlighted the importance of teacher support, collaborative opportunities, and access to Technology and resources in enhancing the effectiveness of blended learning and independent learning practices. These findings contribute to the ongoing discourse on digital-age education and provide insights for educators and policymakers in designing practical instructional approaches that empower students' independent learning skills in the digital era.